Evaluation of Web 2.0 tools in digital journalism: the case of Vilaweb - Hernández Soriano, Francisco; Cristóbal Fransi, Eduard (Historia y Comunicación Social, 2014)
Internet is an ongoing study in which the matching results thereof have settled a firm basis for the establishment and promotion of the media through the Web. For this reason we realized an analysis on VilaWeb because is one of the first digital media appeared in Spain. So, we analyzed their use of Web 2.0 tools on the model devised by Codina (2006) to supplementing the results with other scholars’ analysis.